ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KESADARAN PELAPORAN KECELAKAAN KERJA PADA PEKERJA KONSTRUKSI PROYEK PEMBANGUNAN GEDUNG - Aiman Muhammad Jaidi; Yuliani Setyaningsih; Ida Wahyuni (Jurnal Kesehatan Masyarakat (Undip), 2018)
The construction sector was a sector that contributed to work accidents in Indonesia. Reporting of work accidents that occur by various factors, one awareness. PT.X was a company engaged in construction services. Interviews with foremen, workers' awareness exercised to report work-related accidents were still low. Factors related to awareness of accident work were age, education, work shift, work period, work support and support. The research design used was quantitative with cross-sectional approach. Worker population in PT.X as many as 100 workers. The sampling method used was accidental sampling and result. Data collection used questionnaires. Based on the result of chi-square statistic test, the related variables were education (p-value = 0,021), work shift (p-value = 0,001), and support (p-value = 0,014). The unrelated variables were age (p-value = 0.208, service life (p-value = 0.647), work support (p-value = 0.294).